Tight Frame with Hahn and Krawtchouk Polynomials of Several Variables - Xu, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
Finite tight frames for polynomial subspaces are constructed using monic Hahn polynomials and Krawtchouk polynomials of several variables. Based on these polynomial frames, two methods for constructing tight frames for the Euclidean spaces are designed.